ANALYSIS OF INTEREST IN SAVING IN ISLAMIC BANKING WITH A SOCIAL ENVIRONMENT AS A MEDIATOR IN THE RELATIONSHIP OF RELIGIOSITY AND STUDENT KNOWLEDGE - Noer Aisyah Barlian; Wahyuning Murniati (Jurnal Ilmiah Global Education, 2023)
Saving is a good habit when it comes to financial arrangements, including for college students. The rapid development of sharia economy makes the emergence of various Islamic banking products for this saving activity. This is of course beneficial for students who should have started making financial arrangements.  Although the interest in saving is still lacking, the use of Islamic bank products is quite profitable for their future. The purpose of the study was to analyze the factors that influence students' interest in saving in Islamic banking.  Linear regression is an analysis technique with hypothesis testing to support the conclusions on RStudio. The results of analysis show that the direct impact between religiosity and knowledge of the social environment has a significant effect simultaneously, although religiosity cannot be a predictor of partial saving interest. While the results of the track analysis showed that social environment was able to be a mediator for religious relationships to saving interests, but not for knowledge relationships towards student saving interests in Islamic banking.